A Systematic Review and Meta-Analysis of Endocrine-Related Adverse Events Associated with Immune Checkpoint Inhibitors - de Filette, Jeroen; Andreescu, Corina Emilia; Cools, Filip; Bravenboer, Bert; Velkeniers, Brigitte (Hormone and Metabolic Research, 2019)
Monoclonal antibodies targeting cytotoxic T-lymphocyte antigen-4 (CTLA-4), programed cell death 1 (PD-1), or its ligand (PD-L1) have become the mainstay for advanced malignancies. The incidence of endocrine adverse events provoked by these immune checkpoint inhibitors (ICI) is based on data from randomized controlled trials, which have their drawbacks. PubMed was searched through August 22nd, 2017, by 2 reviewers independently (J.d.F. and C.E.A.). Early phase I/II, phase III experimental trials, prospective and retrospective observational studies were included. The weighted incidence and risk ratio were estimated for hypophysitis, primary thyroid disease, primary adrenal insufficiency, and diabetes mellitus. Their management is discussed in a systematic review. A total of 101 studies involving 19 922 patients were included. Ipilimumab-treated patients experienced hypophysitis in 5.6% (95% CI, 3.9–8.1), which was higher than nivolumab (0.5%; 95% CI, 0.2–1.2) and pembrolizumab (1.1%; 95% CI, 0.5–2.6). PD-1/PD-L1 inhibitors had a higher incidence of thyroid dysfunction – particularly hypothyroidism (nivolumab, 8.0%; 95% CI, 6.4–9.8; pembrolizumab, 8.5%; 95% CI, 7.5–9.7; PD-L1, 5.5%; 95% CI, 4.4–6.8; ipilimumab, 3.8%; 95% CI, 2.6–5.5). Combination therapy was associated with a high incidence of hypothyroidism (10.2–16.4%), hyperthyroidism (9.4–10.4%), hypophysitis (8.8–10.5%), and primary adrenal insufficiency (5.2–7.6%). Diabetes mellitus and primary adrenal insufficiency were less frequent findings on monotherapy. Our meta-analysis shows a high incidence of endocrine adverse events provoked by single agent checkpoint blockade, further reinforced by combined treatment.
Keywords: hypophysitis; thyroiditis; CTLA-4; PD-1; PD-L1